Human Capital, Business Environment Optimization and Foreign Enterprise Innovation - Balakrishnan, Mohamad (International Journal of Accounting and Financial Reporting, 2023)
Under the background that business environment optimization has become a new competitive advantage in cultivating investment and technology introduction, the influence of business environment optimization in developing countries on the innovation willingness of foreign-funded enterprises and the moderating effect of human capital of foreign-funded enterprises are investigated. The results show that: the business environment optimization reduces the willingness of foreign enterprises to carry out technological innovation, process innovation and product innovation, and the average marginal effect increases in turn; The internal mechanism is the reduction of preferential degree of foreign enterprises and the enhancement of competitive power of domestic enterprises brought about by the optimization of business environment. The human capital of foreign-funded enterprises enhances the effect of business environment optimization on their innovation willingness, and this is achieved by enhancing the preferential degree of foreign-funded enterprises, reducing the inhibition of their innovation willingness, and promoting the competitiveness of domestic enterprises by optimizing the business environment. It is further found that the introduction of foreign enterprises has a significant innovation spillover effect, and the absorption capacity of domestic enterprises has a positive regulatory effect.